2010
DOI: 10.1016/j.yexmp.2009.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic modifications induced by RGC-32 in colon cancer

Abstract: First described as a cell cycle activator, RGC-32 is both an activator and a substrate for CDC2. Deregulation of RGC-32 expression has been detected in a wide variety of human cancers. We have now shown that RGC-32 is expressed in precancerous states, and its expression is significantly higher in adenomas than in normal colon tissue. The expression of RGC-32 was higher in advanced stages of colon cancer than in precancerous states or the initial stages of colon cancer. In order to identify the genes that are r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 35 publications
2
38
0
Order By: Relevance
“…RGC-32 plays a role in the immune response which has been determined [29]. Recent studies reported that levels of RGC-32 mRNA in PBMCs were significantly higher in patients with stable SM as compared with patients who had a relapse (active disease) [8] and the RGC-32 protein expressions in macrophages and T cells were significantly increased in the colonic mucosa of patients with inflammatory bowel disease [9]. Our study demonstrates that not only the plasma RGC-32 levels but intracellular RGC-32 expression of CD4 + T cells were also significantly increased in DCM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RGC-32 plays a role in the immune response which has been determined [29]. Recent studies reported that levels of RGC-32 mRNA in PBMCs were significantly higher in patients with stable SM as compared with patients who had a relapse (active disease) [8] and the RGC-32 protein expressions in macrophages and T cells were significantly increased in the colonic mucosa of patients with inflammatory bowel disease [9]. Our study demonstrates that not only the plasma RGC-32 levels but intracellular RGC-32 expression of CD4 + T cells were also significantly increased in DCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In RGC-32-deficient mice, demonstrated that RGC-32 -/-CD4 + T cells exhibited enhanced proliferation, IL-2 production, and Akt phosphorylation as compared with RGC-32 +/+ CD4 + T cells, suggesting a down-regulatory role of RGC-32 under Th0 conditions [7]. Tegla and Vlaicu et al reported increased expression of RGC-32 protein in macrophages, T cells, and astrocytes in the brain of patients with multiple sclerosis (MS) and in the colonic mucosa of patients with inflammatory bowel disease [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…In human diseases, we have reported increased expression of RGC-32 protein in macrophages, T cells, and astrocytes in the brain of patients with multiple sclerosis (MS) and in the colonic mucosa of patients with inflammatory bowel disease (5, 14). A large body of evidence supports the role of proinflammatory Th17 cells in the pathogenesis of MS and other autoimmune diseases (1521).…”
mentioning
confidence: 99%
“…H2BK15ac Acetylated H2BK15 levels are reported to rise after RGC-32 knockdown in colon cancer cell lines (86).…”
Section: H2bk5acmentioning
confidence: 99%